ANALISIS MOLEKULER MDR TB DENGAN TEKNIK SEKUENSING DARI SAMPEL DAHAK SUSPEK TB DI NUSA TENGGARA BARAT - Edy Kurniawan; Maruni Wiwin Diarti; Santy Pristianingrum (Jurnal Kesehatan Prima, 2015)
Abstract: Background: Tuberculosis is one of the tropical diseases that are still of concern to the world , especially with the increasing number of developing multidrug- resistant TB variants. In this study we indetified nucleotide sequence MDR-Tb resistant rifampicin, etambhutol dan isoniazid  from  patient sputum who have suspect tuberculosis infection in West Nusa Tenggara. Methods: This analyze with PCR, sequencing and analysis using Blast Basic Local Alignment Search Tool) from NCBI (National Centre of Biotechnology Information). Result : Twelve samples has been obtained in this study, 9 is positive PCR with TB primer and all of them is still sensitive with rifampicin, etambuthol and isoniazid. Ten sequence sensitive from rpoB, emB and katG has sequencing and Blast analysis, sequence rpoB from TB 5 and TB 6 have similarity with sequence strain M.tb CCDC5079 and TB8 and TB 9 with sequence strain M.tb 96121. emB sequence from sample TB8 and TB9 have similarity with M.tb subsp.tuberculosis partial embB putative arabinosyltransferase mutan 240 exon 1; and TB9 with M.tb strain  2a putative arabinosyltransferase. Sequence from katG from TB8,TB9,TB10 have similarity with M.tb strain 96075. Conclution: MDR-Tb is not found in the studies, with Blast analysis we concluded the Mycobacterium tuberculosis sensitive tuberculosis drugs  sequence from sample study have similarity with M.tb Beijing dan manila Family.